A beautiful blue death eaudiobook - Finch, Charles (Charles Lenox Mystery, 2011)
Charles Lenox, Victorian gentleman and armchair explorer, likes nothing more than to relax in his private study with a cup of tea, a roaring fire and a good book. But when his lifelong friend Lady Jane asks for his help, Lenox cannot resist the chance to unravel a mystery. Prudence Smith, one of Jane's former servants, is dead of an apparent suicide. But Lenox suspects something far more sinister: murder, by a rare and deadly poison. The grand house where the girl worked is full of suspects, and though Prue had dabbled with the hearts of more than a few men, Lenox is baffled by the motive for the girl's death. When another body turns up during the London season's most fashionable ball, Lenox must untangle a web of loyalties and animosities. Was it jealousy that killed Prudence Smith? Or was it something else entirely? And can Lenox find the answer before the killer strikes again—this time, disturbingly close to home?